2022
DOI: 10.3390/molecules27154769
|View full text |Cite
|
Sign up to set email alerts
|

Action of Mangifera indica Leaf Extract on Acne-Prone Skin through Sebum Harmonization and Targeting C. acnes

Abstract: (1) Background: Preclinical studies report that the ethanolic fraction from Mangifera indica leaves is a potential anti-acne agent. Nevertheless, the biological activity of Mangifera indica leaves has scarcely been investigated, and additional data are needed, especially in a clinical setting, for establishing the actual effectiveness of Mangifera indica extract as an active component of anti-acne therapy. (2) Methods: The evaluation of the biological activity of Mangifera indica extract was carried out throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Docking studies were performed with iriflophenone and maclurin, two aglycones of the identified secondary phytomarkers (the fourth was penta-O-galloyl-β-D-glucose; Figure 7), revealing that both compounds bind effectively to the PPARγ transcription factor involved in modulating lipogenesis. Ex vivo experiments (extract at 1%) showed a significant reduction in the production of squalene (-18%), free fatty acids (-8%), and porphyrins [20]. Considering that the lipase activity of C. acnes correlates with acne severity, these studies suggest that the use of these extracts may be useful for the preventive and therapeutic treatment of AV.…”
Section: Anacardiaceaementioning
confidence: 81%
See 1 more Smart Citation
“…Docking studies were performed with iriflophenone and maclurin, two aglycones of the identified secondary phytomarkers (the fourth was penta-O-galloyl-β-D-glucose; Figure 7), revealing that both compounds bind effectively to the PPARγ transcription factor involved in modulating lipogenesis. Ex vivo experiments (extract at 1%) showed a significant reduction in the production of squalene (-18%), free fatty acids (-8%), and porphyrins [20]. Considering that the lipase activity of C. acnes correlates with acne severity, these studies suggest that the use of these extracts may be useful for the preventive and therapeutic treatment of AV.…”
Section: Anacardiaceaementioning
confidence: 81%
“…Mango (Mangifera indica L.) is widely cultivated in tropical regions, especially in India and Thailand, wherein it has been an important medicinal plant in traditional ayurvedic and indigenous medicine for more than 4,000 years. Its parts (especially the leaves) are still commonly used as remedies to treat burns, scalds, and related infections due to its high content of polyphenols [20]. Cashew (Anacardium occidentale L.) is a tropical plant native to South America (especially widespread in the northeastern region of Brazil) rich in tannins, carotenoids and polyphenols [21].…”
Section: Anacardiaceaementioning
confidence: 99%
“…Moreover, G2 increases the diversity of C. acnes , with a modification of the balance between C. acnes phylotypes [ 124 ] Kaempferia parviflora C. acnes -stimulated HaCaT cells and IGF-1 induced sebocytes Kaempferia parviflora modulates the inflammatory signals in C. acnes -stimulated HaCaT cells and inhibits the lipogenesis of sebocytes [ 125 ] Mangifera indica leave Sebocytes and sebaceous glands from skin explants It reduces the C. acnes lipase activity from a severe acne phylotype. Additionally, it protects the microbiota equilibrium [ 126 ] Bee venom (BV) and melittin Models of IGF-1 or C. acnes -induced lipogenic skin disease In the C. acnes -induced mouse model, BV and melittin decrease the transcriptions of genes involved in lipid biosynthesis and inflammation mediated by C. acnes [ 127 , 128 ] …”
Section: Therapeutic Strategies Targeting Skin Microbiota (Especially...mentioning
confidence: 99%
“…Notably, the main component of Kaempferia parviflora , a traditional health-promoting medicine, has been shown to inhibit sebocyte lipogenesis [ 125 ]. Additionally, Mangifera indica leave, a previously reported anti-acne agent, also decrease C. acnes lipase activity, hinting at their potential roles in acne treatment [ 126 ]. Bee venom (BV) and melittin, known for their antibacterial, antiviral, and anti-inflammatory activities in various cell types, have been found to mitigate the upregulation of genes involved in lipid biosynthesis and inflammation triggered by C. acnes .…”
Section: Therapeutic Strategies Targeting Skin Microbiota (Especially...mentioning
confidence: 99%
See 1 more Smart Citation